1984
DOI: 10.1136/gut.25.7.707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and repeated doses of omeprazole on gastric acid and pepsin secretion in man.

Abstract: SUMMARY The effects of omeprazole, a substituted benzimidazole, on gastric acid and pepsin secretion have been studied in twelve healthy subjects. From six to eight hours after a single oral dose of 30 mg, there was a 66% reduction in basal acid output, and a 71*2% reduction in pentagastrin stimulated acid output. A single dose of 60 mg produced a 91.7% reduction in basal acid output and a 95-3% reduction in pentagastrin stimulated acid output. After seven days treatment with 30 or 60 mg daily, there was almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 11 publications
0
32
1
Order By: Relevance
“…We have again demonstrated an increase in antisecretory effect with repeated dosing, accompanied by a rise in the systemic availability of omeprazole as reflected by an increase in AUC in all subjects. As omeprazole is acid-labile (Lind et al, 1983;Howden et al, 1984a) it is probable that the fraction absorbed is increased when there is suppression of acid secretion. When 15 mg omeprazole was given for 5 days the 30% in- ±5.4 ±26 ±6.7 ± 9.5 ± 52 *P < 0.02, **P 0.01, paired t-test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have again demonstrated an increase in antisecretory effect with repeated dosing, accompanied by a rise in the systemic availability of omeprazole as reflected by an increase in AUC in all subjects. As omeprazole is acid-labile (Lind et al, 1983;Howden et al, 1984a) it is probable that the fraction absorbed is increased when there is suppression of acid secretion. When 15 mg omeprazole was given for 5 days the 30% in- ±5.4 ±26 ±6.7 ± 9.5 ± 52 *P < 0.02, **P 0.01, paired t-test.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported on the antisecretory action of 30 and 60 mg in healthy subjects (Howden et al, 1984a (Lind et al, 1983;Howden et al, 1984a). We have therefore examined the pharmacokinetics of omeprazole and its effect on gastric secretion using a lower dose, 10 mg, given for 7 days.…”
Section: Introduction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The doses of omeprazole used in our study are considerably higher than the doses known to produce nearly complete inhibition of acid secretion for 24 hr in man (Howden et al 1984). Investigation of the antisecretory effect of omeprazole after single dose administration in rats showed that the antisecretory effect was not so long in rat as in man and dog (Howden et al 1984). Our study demonstrates that it is possible to inhibit gastric acid secretion effectively for 24 hr in rats with a single dose of omeprazole.…”
Section: Discussionmentioning
confidence: 81%
“…This results in a long-acting inhibitory effect on acid secretion as shown in this study, where acid secretion was inhibited by 85-90% 22-24 hr after 580,umole/kg x day of omeprazole. The doses of omeprazole used in our study are considerably higher than the doses known to produce nearly complete inhibition of acid secretion for 24 hr in man (Howden et al 1984). Investigation of the antisecretory effect of omeprazole after single dose administration in rats showed that the antisecretory effect was not so long in rat as in man and dog (Howden et al 1984).…”
Section: Discussionmentioning
confidence: 94%